Regulatory Challenges and Credibility Issues in Indian Higher Education - Pushkar (International Higher Education, 2025)
<h3 id="the-conversation-surrounding-indian-higher-education-is-often-about-the-governments-overregulation-of-the-sector-and-the-need-for-less-regulation-however-the-problem-appears-to-be-as-much-or-even-more-about-the-lack-of-suitable-and-effective-regulation-which-undermines-the-credibility-of-key-government-regulatory-institutions-as-well-as-that-of-higher-education-institutions" data-pm-slice="1 1 []">The conversation surrounding Indian higher education is often about the government’s overregulation of the sector and the need for less regulation. However, the problem appears to be as much or even more about the lack of suitable and effective regulation, which undermines the credibility of key government regulatory institutions as well as that of higher education institutions.